Method for regulating and controlling performance of ferrite ceramic through 3d-4f super-exchange effect
By introducing 3d-4f super-exchange in ferrite ceramics, spin phonon coupling is formed, and the problem that the coupling effect of spin state and lattice vibration in the prior art is not effectively utilized, and the diversity regulation and applicability of ferrite ceramics are achieved.
Patent Information
- Application Number
- CN202411945531.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-18
AI Technical Summary
In the prior art, the coupling effect between the spin state and lattice vibration (phonon) has not been effectively utilized, resulting in a single material performance and limited application range.
By introducing 3d-4f superexchange in ferrite ceramics, spin phonon coupling is formed by the interaction between iron ion 3d electrons and rare earth ion 4f electrons to regulate the performance of the ceramics. The specific method includes heating the ceramic multiple times, testing its performance parameters at different temperatures, establishing the corresponding relationship between performance parameters and temperature, determining the target temperature based on the target performance parameters, and adjusting the ceramic to the target temperature to achieve the target performance.
By effectively utilizing the spin phonon coupling effect, the performance regulation range of ferrite ceramics is expanded, and the performance diversity and applicability of the materials are improved.
Smart Images

Figure CN119638487A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical fields of intelligent manufacturing, metamaterials and advanced functional materials, and in particular to a method for regulating the performance of ferrite ceramics by using 3d-4f super exchange interaction. Background Art
[0002] The spin-phonon coupling effect refers to the interaction between the spin state of electrons inside a material and lattice vibrations (phonons). In solid materials, the spin of electrons can not only couple with their own orbital motion, but also interact with the vibration modes of the material lattice (i.e., phonons). This coupling will affect the lattice symmetry, defects, and vibration characteristics. The coupling effect is different at different temperatures, resulting in large differences in the magnetoresistance, superconductivity, or magnetoelectric properties of the material at different temperatures. However, in current technology, the coupling effect between this spin state and lattice vibrations (phonons) has not been effectively utilized, resulting in a single material performance and a limited scope of application. Summary of the invention
[0003] The present invention aims to solve or improve the technical problem in the prior art that "the coupling between the spin state and the lattice vibration (phonon) is not effectively utilized, resulting in a single performance of the material".
[0004] The present invention provides a method for regulating the performance of ferrite ceramics by using 3d-4f super exchange, and utilizes the interaction between 3d electrons of iron ions and 4f electrons of rare earth ions to form a spin-phonon coupling structure.
[0005] The present invention provides a method for regulating the performance of ferrite ceramics by 3d-4f super exchange, wherein the chemical formula of the ferrite ceramics is R1 1-x R2 x FeO3, 0≤x≤1, R1 and R2 are both rare earth elements, and the method for regulating the performance of ferrite ceramics by 3d-4f superexchange interaction includes: heating the ferrite ceramics multiple times, and the temperature of the ferrite ceramics after any two heatings is different, and the ferrite ceramics are tested after each heating, and the performance parameters of the ferrite ceramics at different temperatures are determined; a corresponding relationship between the performance parameters and the temperature of the ferrite ceramics is established; based on the input of the target performance parameters of the ferrite ceramics, the target temperature of the ferrite ceramics is determined according to the target performance parameters and the corresponding relationship; the ferrite ceramics are adjusted to the target temperature so that the ferrite ceramics have the target performance.
[0006] In some technical schemes, optionally, x≠0, and x≠1, the method for regulating the performance of ferrite ceramics by 3d-4f superexchange also includes: mixing R12O3, R22O3 and Fe2O3, ball-milling the mixture in anhydrous ethanol once to form a mixture, drying the mixture through an evaporator, calcining the dried mixture at a first preset temperature for a first preset time, ball-milling the calcined mixture for a second time in anhydrous ethanol, drying the mixture after the second ball-milling to obtain an intermediate powder, mixing the intermediate powder and a PVA (Polyvinyl Alcohol) solution, grinding it, and pressing it into a ceramic sheet using a tablet press, placing the ceramic sheet in a muffle furnace, and keeping it warm at a third preset temperature for a third preset time to obtain a ferrite ceramic.
[0007] In some technical schemes, optionally, R1 is Nd element, R2 is Sm element, the first preset temperature is greater than or equal to 900°C and less than or equal to 1000°C; the first preset time is greater than or equal to 5h and less than or equal to 7h; the third preset temperature is greater than or equal to 1200°C and less than or equal to 1300°C; the third preset time is greater than or equal to 5h and less than or equal to 7h.
[0008] In some technical schemes, optionally, before the step of keeping warm at a third preset temperature for a third preset time, it also includes: keeping warm at a second preset temperature for a second preset time; heating the temperature in the muffle furnace to a third preset temperature according to a first heating rate; wherein the second preset temperature is greater than or equal to 600°C and less than or equal to 700°C, the second preset time is greater than or equal to 2h and less than or equal to 4h, and the first heating rate is less than or equal to 3°C / min.
[0009] In some technical solutions, optionally, the performance parameter includes one of the following: a magnetoresistance performance parameter, a superconductivity performance parameter or a magnetoelectric performance parameter.
[0010] In some technical solutions, optionally, the chemical formula of the ferrite ceramic is one of the following: NdFeO3, Nd 0.9 Sm 0.1 FeO3、Nd 0.8 Sm 0.2 FeO3、Nd 0.7 Sm 0.3 FeO3、Nd 0.6 Sm 0.4 FeO3 and Nd 0.5 Sm 0.5 FeO3.
[0011] In some technical schemes, optionally, the test experiment includes one of the following or a combination thereof: four-probe measurement experiment, resistance-temperature curve measurement experiment, magnetoelectric effect measurement experiment, XPS (XPS, X-ray Photoelectron Spectroscopy) test experiment (X-ray photoelectron spectroscopy test experiment), hysteresis loop analysis experiment, UV-diffuse reflection absorption spectrum test experiment, non-polarized Raman spectroscopy analysis experiment.
[0012] In some technical schemes, optionally, the steps of the non-polarized Raman spectroscopy analysis experiment specifically include: using a laser with a wavelength of 532nm to perform a Raman scattering test on ferrite ceramics at room temperature through a microscopic confocal Raman spectrometer to obtain test data, fitting the test data through data fitting software, and obtaining a curve graph.
[0013] In some technical solutions, optionally, the curve graph includes one of the following or a combination thereof: a Raman shift-temperature curve, a half-peak width-temperature curve, a Raman scattering intensity-temperature curve, and a vibration mode curve.
[0014] In some technical schemes, optionally, the test mode of the hysteresis loop analysis experiment is FC-ZFC mode (where FC stands for Field Cooled, which means field cooling in Chinese, and ZFC stands for Zero Field Cooled, which means zero field cooling in Chinese), the external magnetic field is 100Oe, and the temperature range is 2K to 400K.
[0015] Additional aspects and advantages of the present invention will become apparent in the following description or may be learned through practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] The above and / or additional aspects and advantages of the embodiments of the present invention will become apparent and easily understood from the description of the embodiments in conjunction with the following drawings, in which:
[0017] Figure 1 The XRD patterns of NdFeO3 at different sintering temperatures in the embodiment of the present invention are shown;
[0018] Figure 2 (a1) shows a comparison diagram of NdFeO3 of an embodiment of the present invention and a standard spectrum;
[0019] Figure 2 (a2) shows Figure 2 The local enlarged view from 32° to 33° in (a1);
[0020] Figure 2 (b) shows a graph showing the relationship between the lattice constants a, b, c and the lattice volume V and x of an embodiment of the present invention;
[0021] Figure 2 (c) shows the Sm of the embodiment of the present invention 3+ The structure diagram of the replaced ferrite ceramic;
[0022] Figure 2 (d) shows the Sm of the embodiment of the present invention 3+ Crystal structure diagram of ferrite ceramic before replacement;
[0023] Figure 2 (e) shows the Sm of the embodiment of the present invention 3+ Crystal structure diagram of ferrite ceramic after replacement;
[0024] Figure 3 The element content diagram after SEM and EDS scanning of the ferrite ceramic of the embodiment of the present invention is shown;
[0025] Figure 4 (a) shows the full spectrum of the XPS test of the ferrite ceramic of the embodiment of the present invention;
[0026] Figure 4 (b) shows the O1s core spectrum of the ferrite ceramic of the embodiment of the present invention;
[0027] Figure 4 (c) shows the Sm 3d core spectrum of the ferrite ceramic of the embodiment of the present invention;
[0028] Figure 4 (d) shows the Nd 4d core spectrum of the ferrite ceramic of the embodiment of the present invention;
[0029] Figure 5 (a) shows the magnetic moment-temperature curve of NdFeO3 when x=0 in an embodiment of the present invention;
[0030] Figure 5 (b) shows a curve diagram of the magnetic moment-temperature derivative and temperature when x=0 according to an embodiment of the present invention;
[0031] Figure 5 (c) shows the magnetic moment-temperature curve of NdFeO3 when x=0.3 in an embodiment of the present invention;
[0032] Figure 5 (d) shows a curve diagram of the derivative of magnetic moment-temperature and temperature when x=0.3 according to an embodiment of the present invention;
[0033] Figure 5 (e) shows the magnetic moment-temperature curve of NdFeO3 when x=0.5 in an embodiment of the present invention;
[0034] Figure 5(f) shows a curve diagram of the magnetic moment-temperature derivative and temperature when x=0.5 according to an embodiment of the present invention;
[0035] Figure 6 (a) shows the UV-diffuse reflection absorption spectrum of an embodiment of the present invention;
[0036] Figure 6 (b) is a graph showing the relationship between the absorption coefficient, the product of the incident photon frequency and the Planck constant, and the product of the incident photon frequency and the Planck constant of an embodiment of the present invention;
[0037] Figure 7 (a) shows the Raman spectrum of the NdFeO3 polycrystalline ceramic of the embodiment of the present invention at room temperature;
[0038] Figure 7 (b) shows the Nd of the embodiment of the present invention. 1-x Sm x FeO3 Raman spectrum;
[0039] Figure 7 (c) shows a graph showing the change in the peak position of the rare earth ion displacement vibration at low wave numbers in an embodiment of the present invention;
[0040] Figure 7 (d) shows the peak position change of the torsional vibration of the ferrite octahedron at the medium wave number of the embodiment of the present invention;
[0041] Figure 8 (a) shows the temperature-dependent Raman spectrum of NdFeO3 according to an embodiment of the present invention;
[0042] Figure 8 (b) shows one of the spectra of peak position and relative intensity variation with temperature according to an embodiment of the present invention;
[0043] Figure 8 (c) shows the second spectrum of the peak position and relative intensity variation with temperature of an embodiment of the present invention;
[0044] Figure 8 (d) shows a B of an embodiment of the present invention 2g (7) Raman scattering intensity-temperature curve;
[0045] Figure 8 (e) shows a B of an embodiment of the present invention 2g (7) Half-peak width-temperature curve;
[0046] Figure 8 (f) shows an embodiment of the present invention. g (2) B 2g (2) Raman shift-temperature curve in vibration mode;
[0047] Figure 8 (g) shows an embodiment of the present invention. g (3) Raman shift-temperature curve in vibration mode;
[0048] Figure 8 (h) shows an embodiment of the present invention. g (4) Raman shift-temperature curve in vibration mode;
[0049] Figure 8 (i) shows an embodiment of the present invention. g (5) Raman shift-temperature curve in vibration mode;
[0050] Fig. 9 (a) shows the Raman spectra of NdFeO3 at different temperatures according to an embodiment of the present invention;
[0051] Fig. 9 (b) shows the Nd of the embodiment of the present invention. 0.7 Sm 0.3 Raman spectra of FeO3 at different temperatures;
[0052] Fig. 9 (c) shows the Nd of the embodiment of the present invention 0.5 Sm 0.5 Raman spectra of FeO3 at different temperatures;
[0053] Fig. 9 (d) shows the Nd of the embodiment of the present invention. 0.7 Sm 0.3 The relationship between the peak position and Raman shift of FeO3;
[0054] Fig. 9 (e) shows an embodiment of the present invention. g (2) / B 2g (2) Raman shift-temperature curve in vibration mode;
[0055] Fig. 9 (f) shows an embodiment of the present invention. g (4) Raman shift-temperature curve in vibration mode;
[0056] Fig. 9 (g) shows that when X=0, A g (4) Raman shift-temperature curve in vibration mode;
[0057] Fig. 9 (h) shows the case where X=0.3 of the embodiment of the present invention. g (4) Raman shift-temperature curve in vibration mode;
[0058] Fig. 9 (i) shows the embodiment of the present invention when X=0.5. g (4) Raman shift-temperature curve in vibration mode;
[0059] Fig.10 A flow chart showing a method for regulating the performance of ferrite ceramics by 3d-4f superexchange interaction according to an embodiment of the present invention is shown. DETAILED DESCRIPTION
[0060] In order to more clearly understand the above aspects, features and advantages of the embodiments of the present invention, the embodiments of the present invention are further described in detail below in conjunction with the accompanying drawings and specific implementation methods. It should be noted that the embodiments of the present application and the features in the embodiments can be combined with each other without conflict.
[0061] In the following description, many specific details are set forth to facilitate a full understanding of the embodiments according to the present invention. However, the embodiments according to the present invention may also be implemented in other ways different from those described herein. Therefore, the protection scope of the embodiments according to the present invention is not limited to the specific embodiments disclosed below.
[0062] like Fig.10 As shown, the method for regulating the performance of ferrite ceramics by 3d-4f super exchange provided by the present invention, the chemical formula of the ferrite ceramics is R1 1-x R2 x FeO3, 0≤x≤1, R1 and R2 are both rare earth elements, when x is equal to 0, or x is equal to 1, it indicates that there is only one rare earth element in the ferrite ceramic, usually the oxidation state valence of R1 and R2 is +3, but it is not limited to +3, in some cases it may also be other valence states, such as +4, etc. For example, R1 is Nd element, R2 is Sm element, and the method for regulating the performance of ferrite ceramics by 3d-4f super exchange includes the following steps:
[0063] S102: heating the ferrite ceramic for multiple times, wherein the temperatures of the ferrite ceramic after any two heatings are different, and performing a test experiment on the ferrite ceramic after each heating, and determining the performance parameters of the ferrite ceramic at different temperatures;
[0064] S104: establishing a corresponding relationship between the performance parameter and the temperature of the ferrite ceramic;
[0065] S106: Based on the input of the target performance parameters of the ferrite ceramic, according to the target performance parameters and the corresponding relationship, determining the target temperature of the ferrite ceramic;
[0066] S108: Adjusting the ferrite ceramic to a target temperature so that the ferrite ceramic has target performance.
[0067] The method for regulating the performance of ferrite ceramics by 3d-4f super exchange provided by the present invention comprises the following steps: firstly controlling a heating device to heat the ferrite ceramics for multiple times, wherein the temperatures of the ferrite ceramics after any two heatings are different, and then performing a test experiment on the ferrite ceramics by a testing device after each heating, and determining the performance parameters of the ferrite ceramics at different temperatures, wherein the testing device comprises an X-ray diffractometer, a field emission scanning electron microscope, a laser micro-confocal Raman spectrometer, an ultraviolet-visible spectrophotometer, a superconducting quantum interferometer, a precision impedance analyzer, a YAG (Yttrium Aluminum Garnet) laser (yttrium aluminum garnet laser), etc. For example, a hysteresis loop analysis experiment is used to analyze the magnetic moment parameters of ferrite ceramics at different temperatures, and at the same time, a corresponding relationship between the magnetic moment parameters and the temperature of ferrite ceramics is established. In this way, according to the demand, when the ferrite ceramics are required to have specific magnetic moment performance, due to the corresponding relationship between the magnetic moment parameters and the temperature of the ferrite ceramics, the target temperature of the ferrite ceramics can be quickly located, thereby adjusting the ferrite ceramics to the target temperature so that the ferrite ceramics have the target performance.
[0068] In some technical solutions, optionally, the heating device heats the ferrite ceramic multiple times in a heating range of 0K to 800K, and a heating gradient of 5K to 20K, for example, 20K, that is, starting from 0K, the ferrite ceramic is heated by 20K each time, and then the performance parameters of the ferrite ceramic at different temperatures are determined by testing the ferrite ceramic, so that the relationship curve between the performance parameters and the ferrite ceramic temperature can be fitted for all measured performance parameter data, so that the performance of the ferrite ceramic can be quickly adjusted according to the needs later. In addition, the present invention adopts Nd 1-x Sm x FeO3 is used as ferrite ceramics because Sm 3+ The influence of doping on the lattice vibration of NdFeO3 ceramics is more obvious, thereby increasing the range of regulating the performance of ferrite ceramics, making the ferrite ceramics of the present invention suitable for a wider range of use scenarios. 3+ and Fe 3+ There is also a strong correlation between them, and the fluctuation is more obvious with the change of temperature, which further improves the range of regulating the performance of ferrite ceramics.
[0069] It should be understood that this application involves Nd 1-x Sm xVarious tests were conducted on the appearance and performance parameters of FeO3 ferrite ceramics. Among them, the crystal structure and phase composition of the ceramic samples were tested at room temperature by X-ray diffraction (XRD). Before the test, the samples were fully ground, passed through a 200-mesh sieve, and measured using a Cu-Kα target. The test range was 10°-90° and the scanning speed was 5° / min. The micromorphology was characterized by a field emission scanning electron microscope (SEM, Scanning Electron Microscope). The Raman spectrum of the sample was tested at room temperature using a laser microscopic confocal Raman spectrometer and a 532nm Nd:YAG (Yttrium Aluminum Garnet) laser (yttrium aluminum garnet laser), and the test data was analyzed using Labspec5 software (Raman spectrum analysis software). The state of the elements in the ceramics was analyzed using X-ray photoelectron spectroscopy, and Avantage and XPSPeak software (XPS peak analysis software) were used in the data processing process. The valence band of the samples was analyzed using UV-VIS-DRS (Ultraviolet-Visible Diffuse Reflectance Spectroscopy). The dielectric spectrum of the samples at room temperature at 40Hz-110MHz was tested by a precision impedance analyzer. The magnetic properties were characterized by the magnetic moment-temperature module and the magnetic moment-magnetic field module of the superconducting quantum interference device (SQUID).
[0070] 3d-4f superexchange is the strong interaction between three-dimensional electrons and 4f electrons.
[0071] In some technical schemes, optionally, x≠0, and x≠1, the method for regulating the performance of ferrite ceramics by 3d-4f superexchange also includes: mixing R12O3, R22O3 and Fe2O3, and ball-milling them once in anhydrous ethanol to form a mixture, drying the mixture through an evaporator, calcining the dried mixture at a first preset temperature for a first preset time, ball-milling the calcined mixture for a second time in anhydrous ethanol, drying the mixture after the second ball-milling to obtain an intermediate powder, mixing the intermediate powder and PVA solution, grinding them, and pressing them into ceramic sheets using a tablet press, placing the ceramic sheets in a muffle furnace, keeping them warm at a second preset temperature for a second preset time, heating the temperature in the muffle furnace to a third preset temperature according to a first heating rate, and then keeping the ceramic sheets warm at the third preset temperature for a third preset time to obtain ferrite ceramics.
[0072] In this technical solution, since there are two different rare earth elements in the ferrite ceramic, different sintering temperatures can be determined according to different rare earth elements during the preparation process, that is, the first preset temperature is less than the third preset temperature, and the first preset temperature is used for sintering the rare earth element with the lower sintering temperature among the two different rare earth elements, while the third preset temperature is used for sintering the rare earth element with the higher sintering temperature among the two different rare earth elements. The intermediate powder is the product of sintering between Fe2O3 and the rare earth element with the lower sintering temperature among the two different rare earth elements. For example, R1 is Nd element and R2 is Sm element, and the intermediate powder is NdFeO3 powder.
[0073] Optionally, to prepare Nd 1-x Sm x Taking FeO3 as an example, the first preset temperature is greater than or equal to 900°C and less than or equal to 1000°C, for example, 900°C, 950°C or 1000°C, the first preset time is greater than or equal to 5h and less than or equal to 7h; for example, 5h, 6h or 7h, the second preset temperature is greater than or equal to 600°C and less than or equal to 700°C, for example, 600°C, 650°C or 700°C; the second preset time is greater than or equal to 2h and less than or equal to 4h, for example, 2h, 3h or 4h; the third preset temperature is greater than or equal to 1200°C and less than or equal to 1300°C, for example, 1200°C, 1250°C or 1300°C; the third preset time is greater than or equal to 5h and less than or equal to 7h, for example, 5h, 6h or 7h; the first heating rate is less than or equal to 3°C / min, for example, 2°C / min.
[0074] In this technical solution, Nd can be prepared by a standard solid phase reaction method. 1-x Sm x FeO3 (x=0, 0.1, 0.2, 0.3, 0.4, 0.5) ceramics. Specifically, Nd2O3, Sm2O3 and Fe2O3 are weighed and mixed according to the corresponding molar ratio, ball-milled in anhydrous ethanol for 24 hours, and then dried by a rotary evaporator. The mixture powder obtained after drying is pre-calcined at 1000°C for 6 hours in a muffle furnace, and then the pre-calcined powder is added with anhydrous ethanol as a medium and ball-milled for 24 hours with a proportional number of ball milling beads of different diameters. The ball-milled powder is dried to obtain NdFeO3 powder, a PVA solution with a mass fraction of 5% is added, and it is fully ground in a mortar, and a ceramic sheet with a diameter of 14 mm is pressed by a tablet press at a pressure of 8 tons (holding time 3 minutes), and then the ceramic sheet is heated to 600°C in a muffle furnace for 3 hours to remove binder, and then sintered at T=1225°C, 1245°C, 1265°C, 1285°C, 1305°C, and 1325°C, respectively. After holding for 6 hours, it is cooled to room temperature with the furnace to obtain Nd 1-x Sm xFeO3 (0≤x≤0.5), wherein the heating rate is 2°C / min.
[0075] The present invention also discusses the sintering temperature. Specifically, the preparation process of ferrite ceramics covers two parts: pre-firing and sintering. In the solid-phase reaction method, the main purpose of pre-firing is to remove possible organic matter, bound water, carbonates and volatile impurities, so that the oxides undergo thermochemical reactions to form the desired solid solution, and to reduce the huge volume shrinkage that occurs when the ceramic pieces are fired. In order to obtain high-quality NdFeO3 samples, it is first necessary to make reasonable selections of the important parameters involved in the pre-firing process to eliminate the adverse effects caused by mismatched preparation conditions. In order to explore the sintering characteristics of NdFeO3, we first start with the selection of the pre-firing temperature, and use XRD spectra to perform phase identification and crystallographic analysis on the products obtained after the mixture has been pre-firing at different temperatures. The XRD spectra of the products obtained at different pre-firing temperatures are shown in Figure 2. Figure 1 As shown, the mixed product may have absorbed a certain amount of water during the ball milling process, and formed some Nd(OH)3 during the drying process. At room temperature, it was observed that there were three phases in the mixture powder after ball milling and drying, namely Nd(OH)3, Nd2O3 and Fe2O3. When the pre-firing temperature is lower than 600°C, the diffraction peaks of the mixture hardly change. When the temperature is higher than 700°C, it can be observed that the intensity of the diffraction peak of the Nd2O3 crystal plane is significantly reduced, and at the same time, the diffraction peak of the crystal plane of the target phase NdFeO3 appears. As the pre-firing temperature continues to increase, the relevant diffraction peaks of the NdFeO3 phase gradually become stronger. When the pre-firing temperature is 1000°C, except for a small amount of excessively added Nd2O3 as an impurity residue (often difficult to avoid by solid phase reaction preparation), the NdFeO3 phase occupies all, and at this time, the NdFeO3 powder for sintering has been obtained by pre-firing. Therefore, the present application can select 1000°C as the pre-firing temperature.
[0076] In addition, the present application also analyzes the purity of the prepared NdFeO3 powder, such as Figure 2 (a1), where Figure 2 In (a1), the vertical lines are the lines connecting the peaks of the standard sample, while the lines connecting the peaks of the present application are basically consistent with the vertical lines of the standard. The two match well, indicating that the purity of NdFeO3 prepared in the present application is relatively high. Figure 2 As can be seen from (a1), all samples belong to the Pbnm space group (where Pbnm is a space group representing the crystal structure, P represents the primitive unit cell, b represents a slip plane in the b-axis direction, n represents a diagonal slip plane in the ac plane, and m represents a mirror plane in the ab plane), Sm 3+The substitution of Sm did not change the original unit cell type, so no increase or decrease in the number of X-ray diffraction peaks was observed. 3+ The effect of substitution on the crystal structure of NdFeO3 was investigated by locally amplifying the diffraction peak between 32° and 33.0°. Figure 2 As shown in (a2), accompanied by Sm 3+ With the gradual increase of the content in the lattice, the main diffraction peak shifted significantly to the right.
[0077] In addition, if Figure 2 As shown in (b), with the increase of Sm substitution, the lengths of the a-axis and c-axis decrease monotonically, while the b-axis hardly changes relative to the changes of the a-axis and c-axis, and only increases slightly within a very small range. 3+ With Nd 3+ The ionic radius is close to (r Sm3+ =1.079, r Nd3+ =1.109), so Sm 3+ The substitution does not introduce significant distortion, which is consistent with experimental expectations. Figure 2 (c) Figure 2 (d) and Figure 2 (e) shows that NdFeO3 and Sm 3+ The crystal structure of NdFeO3 before and after substitution, such as Figure 2 (d) and Figure 2 (e) It can be seen that a Sm 3+ Replaced an Nd 3+ The crystal structure after substitution is still a perovskite-like structure with GdFeO3 type distortion, belonging to the Pbnm space group, in which Fe 3+ The ion is located at the center of the oxygen octahedron, with six O 2- The ion coordination is arranged in a pseudocubic structure, Sm 3+ With Nd 3+ The ions are randomly distributed on the R sites in RFeO3 in another pseudocubic substructure.
[0078] Needs further explanation, Figure 2 (d) and Figure 2 (e) Schematic diagram of the crystal structure, drawn using VESTA software (Visualization for Electronic and Structural Analysis, a 3D visualization software widely used in the field of materials science research). The octahedron is the FeO6 octahedral framework, and the Fe 3+ The cation is at the center of the octahedron.
[0079] In addition, for all Nd 1-x Smx The surface morphology and EDS (Energy Dispersive Spectroscopy) spectrum of FeO3 (0≤x≤0.5) samples were tested, such as Figure 3 As shown, with Sm 3+ As the content increases, the surface morphology of the ceramic does not change significantly, the grain boundaries are clear, and the dense state is maintained. Due to the inaccurate selection of the sintering temperature, the intermediate components have grown grains, and the number of grains of 5μm-10μm has increased, indicating that the sintering temperature and sintering time may be too high. From the EDS energy spectrum, it can be found that the element distribution of all samples is very uniform. Figure 3 The percentage figures in the figure are the element contents measured by EDS signals. The test data show that the solid phase reaction method has successfully prepared well-crystallized, dense and uniform Nd 1-x Sm x FeO3 ceramic samples.
[0080] In addition, this application also analyzes Sm 3+ Effect of doping on oxygen vacancy content and Fe 3+ The effect of valence state, specifically, on all Nd 1-x Sm x FeO3 samples were subjected to XPS testing. In order to reduce the error introduced by sample surface contamination, Ar + Ion etching of sample surface. Figure 4 (a) is the test spectrum of the full XPS spectrum, in which the C1s peak is used for calibration. In addition to the C1s peak, the peaks generated by Nd, Sm, Fe, and O elements can be clearly observed. There are no impurity element peaks within the test range. Since the Nd 3d core energy level overlaps with the OKLL peak, the Nd 4d core energy level is scanned carefully to obtain relevant results about the Nd element of the sample. Oxygen vacancies are one of the objects we focus on. Nd 1-x Sm x The O1s core spectrum of FeO3 ceramics is generally believed to be derived from the low binding energy oxygen peak at around 529.5 eV. L ), when oxygen in the complete lattice overflows to produce oxygen vacancies, due to the loss of O 2- , which will increase the binding energy and generate vacancy oxygen (O-vacancy, V O ) and O-absorption (O) at around 532.4 eV. A ),like Figure 4 (b) It can be seen that as Sm 3+With the increase of doping amount, the O1s narrow spectrum of the sample has changed significantly. The lattice oxygen peak at low binding energy has become stronger, while the vacancy oxygen and adsorbed oxygen peaks at high binding energy have become weaker. It is generally believed that XPS only reflects the information of the surface of the test sample, and there is often a certain difference between the surface state and the interior of the sample. Here, only the trend change of the O1s spectrum is used to judge that there may be an increase in lattice oxygen and a decrease in oxygen vacancies. Further, Figure 4 (c) and Figure 4 (d) shows the core spectra of Sm 3d level and Nd 4d level for all samples. 3+ The two spin-orbit splitting peaks are located at 1083.1eV and 1109.5eV respectively. With the increase of doping amount, the spectrum peak intensity of Sm 3d energy level is obviously enhanced. At the same time, it can also be observed that the spectrum peak intensity of Nd 4d energy level gradually decreases, which is consistent with the results of EDS.
[0081] In some technical solutions, optionally, the performance parameter includes one of the following: a magnetoresistance performance parameter, a superconductivity performance parameter or a magnetoelectric performance parameter.
[0082] In this embodiment, the change of the lattice structure of the ferrite ceramic will cause the change of the magnetoresistance performance parameter, superconductivity performance parameter or magnetoelectric performance parameter of the ferrite ceramic, thereby regulating the performance of the ferrite ceramic.
[0083] The magnetic properties of the ferrite ceramic of the present invention at different temperatures are discussed below. It should be understood that the characteristic of antiferromagnetic materials is that their internal spin arrangement makes the adjacent spins in opposite directions, thereby canceling each other out, resulting in a weakened net magnetic moment. However, under the action of an external magnetic field of sufficient strength, this spin arrangement can be changed. Specifically, under a lower external magnetic field, the antiferromagnetic material exhibits a magnetization intensity-magnetic field intensity relationship similar to that of a paramagnetic material, and when the external magnetic field is enhanced to a higher level, a hysteresis loop shape similar to that of a ferromagnetic material appears.
[0084] The present invention is tested by a hysteresis loop analysis experiment, the test mode is FC-ZFC mode (wherein, FC stands for Field Cooled, which means field cooling in Chinese, and ZFC stands for Zero Field Cooled, which means zero field cooling in Chinese), the external magnetic field is 100Oe, the temperature range is 2K to 400K, and the magnetic moment-temperature curve of the ferrite ceramic is as follows Figure 5 (a) Figure 5 (c) and Figure 5 As shown in (e), the relationship between the magnetic moment-temperature derivative and temperature is as follows: Figure 5 (b) Figure 5 (d) and Figure 5 (f), where Figure 5 (a) and Figure 5 (b) corresponds to x being 0, that is, Figure 5 (a) and Figure 5 (b) The corresponding substance is NdFeO3, Figure 5 (c) and Figure 5 (d) corresponds to x = 0.3, that is, Figure 5 (c) and Figure 5 (d) The corresponding substance is Nd 0.7 Sm 0.3 FeO3, Figure 5 (e) and Figure 5 (f) The corresponding substance is Nd 0.5 Sm 0.5 FeO3, it can be clearly seen from these figures that within this temperature range, the ferrite ceramics of the present application have three magnetic structures, namely, low temperature phase Γ2-G z F x , transition phase Γ 24 -G xz F xz With high temperature phase Γ4-G x F z , (where Γ2, Γ 24 and Γ4 are three phases, G represents the Goodman magnetic order, in which the magnetic moments of adjacent unit cells are in opposite directions, F represents the Ferro type magnetic order, in which all magnetic moments are in the same direction, and xyz represents the three directions abc, respectively. z F x For example, it represents that in the low temperature phase, the c direction is the Goodman magnetic order and the a direction is the Ferro type magnetic order).
[0085] According to the hysteresis loop analysis experiment, at low temperature, the rare earth ion Nd 3+ The magnetic moment of Nd is the main contribution. As the temperature increases, 3+ The magnetic moment of Fe 3+ The magnetic moment provided by Nd becomes the main contribution. 3+ with Fe 3+ The magnetic moments of the magnetic sub-lattice are antiparallel and equal in magnitude, resulting in a magnetic compensation point T comp .
[0086] It can be seen that based on the analysis of the magnetism of ferrite ceramics in this application, the magnetic moment of ferrite ceramics can be regulated by controlling the temperature of ferrite ceramics, so as to facilitate subsequent rapid application in different usage scenarios.
[0087] In addition, the present invention also explores Sm 3+ The influence of doping on the conductive behavior of NdFeO3 ceramics 1-x Sm xFeO3 (0≤x≤0.5) was tested for UV-diffuse reflectance absorption spectrum, and the data of different samples after testing were normalized to draw a curve graph, such as Figure 6 (a) and Figure 6 As shown in (b), the absorption spectrum data is processed using the following formula, and the band gap of the sample is calculated using the Tauc Plot method:
[0088] (αhv) 1 / m =B(hv-R g );
[0089] Where α is the absorption coefficient, v is the frequency of the incident photon, h is Planck's constant, m is the band gap type of the material. For direct band gap materials, m = 1 / 2, for indirect band gap materials, m = 2, B is the proportional constant, which depends on the specific properties of the material and can be obtained by fitting experimental data. Rg represents the band gap energy.
[0090] according to Figure 6 (a) and Figure 6 (b) It can be seen that the absorption spectra of different components in the ultraviolet-near infrared band are basically consistent, and the band gaps are also basically consistent. Since the band gap of SmFeO3 is close to that of NdFeO3, and Sm 3+ The lattice distortion caused by doping is smaller than the twisting of FeO6, which may lead to a smaller band gap change. At the same time, the powder samples of all components are reddish brown, and the visible light wavelength corresponding to this color is around 530nm-600nm, so the absorption of almost all RFeO3 material powders around 530nm will drop rapidly.
[0091] In some technical solutions, optionally, the chemical formula of the ferrite ceramic is one of the following: NdFeO3, Nd 0.9 Sm 0.1 FeO3、Nd 0.8 Sm 0.2 FeO3、Nd 0.7 Sm 0.3 FeO3、Nd 0.6 Sm 0.4 FeO3 and Nd 0.5 Sm 0.5 FeO3.
[0092] In some technical schemes, optionally, the test experiment includes one of the following or a combination thereof: a four-probe measurement experiment, a resistance-temperature curve measurement experiment, a magnetoelectric effect measurement experiment, an XPS test experiment, a hysteresis loop analysis experiment, an ultraviolet-diffuse reflectance absorption spectrum test experiment, and a non-polarized Raman spectrum analysis experiment.
[0093] In this technical solution, the four-probe measurement experiment is mainly used to measure the magnetoresistance of ferrite ceramic magnets. The specific measurement steps are: prepare a ferrite ceramic sample of standard size to ensure that the surface is flat and clean. Distribute four probes evenly on the sample, two of which are used as current probes and the other two as voltage probes. Connect the current probe to a constant current source and the voltage probe to a voltmeter or data acquisition system. Place the sample in an environment with an adjustable magnetic field, such as an electromagnet or a superconducting magnet. Record the resistance value of the sample under different magnetic field strengths. Usually start from zero magnetic field and gradually increase the magnetic field strength, and record the resistance value at each step. Draw a curve of resistance changing with magnetic field and calculate the magnetoresistance effect.
[0094] The resistance-temperature curve measurement experiment is mainly used to measure the superconductivity of ferrite ceramic magnets. The specific measurement steps are as follows: prepare a ferrite ceramic sample of standard size and ensure that the surface is flat and clean. Evenly distribute four probes on the sample, two of which are used as current probes and the other two as voltage probes. Connect the current probe to a constant current source and the voltage probe to a voltmeter or data acquisition system. Place the sample in a low-temperature environment, such as a liquid helium dewar or a cryostat. Gradually lower the temperature from room temperature and record the resistance values at different temperatures. Draw a curve of resistance versus temperature to determine the critical temperature, that is, the temperature point at which the resistance suddenly drops to zero, thereby determining the superconductivity of the ferrite ceramic magnet.
[0095] The magnetoelectric effect measurement experiment is mainly used to measure the magnetoelectric properties of ferrite ceramics. The specific measurement steps are as follows: prepare a ferrite ceramic sample of standard size and ensure that the surface is flat and clean. Apply conductive silver paste on two opposite surfaces of the sample to form electrodes. Connect one electrode to the input of a phase-locked amplifier and the other electrode to ground. Place the sample in an environment with an adjustable magnetic field, such as an electromagnet or a superconducting magnet. Use a signal generator to generate an alternating magnetic field, and the frequency is usually in the range of tens of hertz to several kilohertz. Use a phase-locked amplifier to measure the electric polarization response of the sample under the alternating magnetic field. Plot a curve of the electric polarization response versus magnetic field strength and calculate the magnetoelectric coefficient.
[0096] XPS testing experiments are mainly used to measure the chemical composition of ferrite ceramic magnets, determine the element composition and content on the sample surface, analyze the chemical valence and chemical environment of the elements, and also to determine the surface structure and provide detailed information about the surface atomic layer, including the thickness and structure of the oxide layer.
[0097] The hysteresis loop analysis experiment is used to measure the magnetic properties of ferrite ceramic magnets: including coercive force, remanence, saturation magnetization, etc. It is also used to measure the magnetic domain structure and provide information about the material's magnetic domain structure and magnetization process.
[0098] The UV-diffuse reflection absorption spectrum test experiment is mainly used to measure the optical band gap of ferrite ceramic magnets, reflect the photoelectric properties of the material, determine the surface state and defects, and provide information about the surface state and defects.
[0099] Unpolarized Raman spectroscopy experiments are used to provide detailed information about the crystal structure of a material, including lattice vibration modes and symmetries, determine the chemical composition of the material, including the presence of different chemical bonds and groups, and also to reveal the stress and strain state within the material.
[0100] Optionally, the steps of the non-polarized Raman spectroscopy analysis experiment specifically include: using a laser with a wavelength of 532nm to perform a Raman scattering test on ferrite ceramics at room temperature through a microscopic confocal Raman spectrometer to obtain test data, fitting the test data through data fitting software, and obtaining a curve graph. Optionally, the curve graph includes one of the following or a combination thereof: Raman shift-temperature curve, half-peak width-temperature curve, Raman scattering intensity-temperature curve, vibration mode curve. Optionally, the test mode of the hysteresis loop analysis experiment is FC-ZFC mode, the external magnetic field is 100Oe, and the temperature range is 2K to 400K.
[0101] In these technical solutions, the applicant studied the spin-phonon coupling effect of NdFeO3 based on Raman spectroscopy analysis experiments, and explored the influence of different temperatures on the spin-phonon coupling effect of NdFeO3, as follows:
[0102] Raman spectroscopy is an efficient method for in-depth study of local lattice symmetry, defects, and lattice vibrations in crystals. It is widely used in the study of condensed matter. Raman scattering tests were performed on NdFeO3 ceramics at room temperature using a laser with a wavelength of 532nm through a microscopic confocal Raman spectrometer. The peaks were fitted using Labspec5 software and compared with the calculation results in other literature. The non-polarized Raman spectrum of NdFeO3 ceramics at room temperature is shown in Figure 7 (a) Here, Origin software (a data analysis and drawing software) is used to fit the part with obvious peak shape, and the peak shape used in the fitting process is the Lorentz line shape.
[0103] According to the principle of symmetry, NdFeO3 ceramics belong to the Pbnm space group, in which the irreducible form of the center of the Raman active Brillouin zone is:
[0104] Γ=7A g +5B 1g +7B 2g +5B 3g ;
[0105] Where Γ is the center of the Brillouin zone, A g , B1g , B 2g and B 3g There are 4 different vibration modes.
[0106] In the analysis of Raman scattering, it is theoretically expected that there are 24 Raman-active vibration modes, but in actual operation, due to technical limitations and the complexity of physical phenomena, it is often impossible to clearly distinguish all 24 vibration peaks directly from the spectrum. This situation is mainly attributed to two factors: first, the Raman signal intensity generated by some vibration modes is too low, so that it exceeds the detection threshold of the instrument used in the experiment and cannot be captured; second, the Raman peaks corresponding to different vibration modes may overlap, making it difficult to distinguish and resolve independent peaks on the spectrum. For verification and comparison, we compared the NdFeO3 Raman spectrum data measured at room temperature with the results based on calculations in the literature, as well as the data reported in other experimental literature, and summarized them in the table for comparison. The analysis results show that the test data is highly consistent with the calculated predictions and past experimental results, which further confirms the accuracy and reliability of the test results. It can also be found that in the low wavenumber band (<200cm -1 ) is related to the stretching vibration of Nd and O. -1 -350cm -1 ) is related to the torsion angle of FeO6, (350cm -1 -500cm -1 ) is related to the vibration of O, and the high wave number band (>500cm -1 ) is related to Fe-O stretching vibration. The reasonable and accurate assignment of these vibration modes and peak positions is an important guarantee for subsequent research.
[0107] By correlating the peak position with the vibration mode, it is pointed out that the vibration modes in different wave number bands are related to the vibration of different atoms in NdFeO3 ceramics. 3+ The crystal structure distortion caused by doping was tested by Raman spectroscopy of all component samples at room temperature, and it was found that their peak shapes were very similar and the number of peaks did not change, which was consistent with the XRD test results, indicating that the crystal maintained the symmetry of Pbnm during the doping process. -1 -200cm -1 ) is related to the displacement vibration of rare earth ions, and the mid-wavelength band (200cm -1 -500cm -1 ) vibration peaks are related to the bending, torsional and stretching vibrations of the ferrite octahedron. -1 -700cm -1 ) vibration peaks come from various vibration modes of Fe-O bonds.3+ The influence of doping on the lattice vibration of NdFeO3 ceramics is divided into seven peak intervals. 3+ With the increase of content, the peak position hardly changes. Figure 7 As shown in (d), the x and z direction vibration displacements of rare earth ions remain stable. 3+ As the content increases, the peak position shifts linearly. For details, see Figure 7 (b) and Figure 7 (c). This shows that the iron oxide octahedron in Sm 3+ Distortion occurs during the doping process, for example
[101] pc and
[010] pc The torsion angle in the direction increases, causing the Raman peaks in the middle wave number band to collectively red shift. Among them, the
[101] pc direction is the direction of the diagonal of the X-axis and the Z-axis, the
[010] pc direction is the direction of the Y-axis, and the X-axis, Y-axis and Z-axis correspond to the three directions abc. In the high wave number band, it can be seen that at room temperature, the vibration mode of NdFeO3 ceramics in this range is sharp, and the introduction of Sm 3+ After that, the peak intensity is significantly weakened and the vibration of Fe-O is significantly suppressed.
[0108] In order to calculate the effect of the magnetic exchange interaction on the phonon behavior, the purely anharmonic temperature dependence of the frequencies of the different modes is described by the following model:
[0109] ω(T)=ω(0)-C(1+2 / (e x -1)) (5)
[0110] Where ω(T) and ω(0) are the frequencies of the optical mode at temperature T and 0 K, respectively, and x = hω0 / k B T, e is a natural constant, h is Planck's constant, ω0 is the characteristic frequency of the vibration mode, k B is the Boltzmann constant, and C is the anharmonic coefficient obtained by fitting.
[0111] A temperature region with high data quality and relatively stable is selected. By making the best fit to the adjustable parameters C and ω(0), the expected evolution of the Raman peak shift and half-peak width change with increasing temperature can be plotted. The contribution of the spin-phonon coupling effect can be clarified by deducting the contribution from the temperature increase.
[0112] Figure 8 (a) and Figure 8(b) shows the temperature-dependent Raman spectrum of NdFeO3 in the temperature range of 80K-780K. By preprocessing the Raman data, the dependence of the Raman vibration peak on temperature is analyzed. The study found that as the temperature increases, some phonon bands gradually soften and move at different rates, and some sharp peaks in the low wavenumber range merge. The increase in temperature causes the energy fluctuation to become larger, and the peak positions of some characteristic peaks overlap and become difficult to identify. The number of Raman characteristic peaks observed at high temperatures decreases, indicating that the symmetry of the crystal may increase with increasing temperature and the degree of anisotropy decreases. At the same time, some characteristic peaks show a phenomenon of first redshift and then blueshift during the temperature increase. According to equation (5), the Raman shift is described as a decreasing function of temperature. It can be inferred that this is closely related to the spin-phonon coupling effect. Figure 8 (c) with Figure 8 (e) Plot B 2g (7) The relationship between the mode Raman shift and half-peak width and temperature. The value of the error bar comes from the error in the fitting process. When the fitting error is less than the spectral repeatability, the error bar is not displayed. According to the test results, it can be found that the spin-phonon coupling phenomenon occurs in the range below the spin reorientation phase transition temperature. At the same time, when passing through the Neel temperature point, the NdFeO3 Raman test results show that there is no spin-phonon coupling effect, which is different from RMnO3 materials and two-dimensional systems such as CrBr3. This is explained by the lack of Jahn-Teller distortion in RFeO3. Continuing the experiment, it was found that B 2g (7) The peak position and half-maximum width of the mode shift abnormally near 160 K, indicating the existence of spin-phonon coupling in this temperature range. Figure 8 (d) shows B 2g (7) The relationship between the intensity of the vibration mode and temperature. It can be seen that as the temperature increases, the Raman scattering intensity decreases rapidly. When the temperature approaches the Neel temperature, the Raman intensity remains at a stable value. In this process, the relationship between the Raman scattering intensity and temperature can be well fitted by an exponential function. The results of this study show the strong correlation between the Fe-O vibration and the magnetic ordering temperature in the NdFeO3 material.
[0113] After discussing the obvious changes in B 2g (7) vibration mode, we can see that Nd 3+ Ion x, z direction oscillation mode A g (2) With B 2g (2) To explore the effect of Nd 3+ Ion-involved spin-phonon coupling. Figure 8 (f) shows that below 110K, two types of Nd 3+The vibration modes all experienced a slight frequency reduction, which is consistent with previous reports and further verifies the reliability of the experimental conditions and test samples. This small frequency reduction is believed to be due to the Nd 3+ This small frequency reduction is believed to be due to the coupling between Nd 3+ There is evidence of coupling with phonons. g (3) Similar phenomena were found in the model. Figure 8 (g), Due to the large data deviation, three outliers around 400K are removed. g (3) As a rotational vibration mode of FeO6, the lattice vibration represented by it is similar to that of Nd 3+ There is no direct correlation, but it is also a deviation from the typical warming effect. g (3) The mode is proportional to the rotation angle of FeO6 in RFeO3, and the Dzyaloshinsky-Moriya effect in RFeO3 determines the adjacent Fe 3+ Therefore, it can be inferred that FeO6 changes the coupling pathway between Fe-O-Nd during rotation, which leads to the g (3) The Raman shift of the peak position shows abnormal evolution at low temperature. It can be found that the initial temperature of the atypical thermal behavior of the Raman frequency exhibiting spin-phonon coupling characteristics in NdFeO3 occurs at the spin reorientation temperature T SR Although it was previously believed that the spin reorientation phase transition in NdFeO3 is affected by Fe 3+ Orderly influence rather than Nd 3+ However, Raman test results show that below the spin reorientation temperature, Nd 3+ with Fe 3+ There is a strong correlation between them. 3+ The displacement and FeO6 rotation together show spin-related Raman scattering abnormal behavior. This abnormal shift is about 1cm in the test temperature range. -1 -3cm -1 . Figure 8 (h) and Figure 8 (i) The A g (4) With A g (5) Vibrational modes. Although they are both FeO6-related vibrational modes, they both exhibit spin-independent pure temperature-responsive Raman scattering behavior during the heating process. This is also true for other RFeO3. Not all FeO6-related modes exhibit coupling between Fe-OR, indicating that the coupling is strongly anisotropic.
[0114] We discussed the doping of Sm 3+ Spin-phonon coupling effect of NdFeO3. 1-xSm x The temperature-dependent Raman results of FeO3 (x = 0, 0.3 and 0.5) are as follows: Fig. 9 (a) Fig. 9 (b) and Fig. 9 (c) is shown. Unlike NdFeO3, which has an initial blue shift temperature of 110K, Nd 0.7 Sm 0.3 FeO3 at 100cm -1 -500cm -1 The initial temperature of most characteristic peaks in the blue-shifted Raman shift range increases to around 200 K. 3+ and Nd 3+ The magnetic properties of Nd are different, and it can be observed that the spin orientation temperature of the two is very different. 0.7 Sm 0.3 T of FeO3 SR in the range of 260K to 300K. These findings suggest that regulation of T SR It can be used to control phonons in NdFeO3. 2g (7) mode shows the same temperature dependence trend as NdFeO3, and B can also be observed at low temperatures. 3g (5) vibration mode. The above behavior change is due to Sm 3+ The introduction of Nd ions changes the vibration of Fe-O bonds and FeO6 in the lattice. 0.5 Sm 0.5 FeO3 was subjected to temperature-dependent Raman spectroscopy to further determine T SR The effect of temperature change on the spin-phonon coupling effect. The test results are as follows Fig. 9 As shown in (c), compared with the x=0 and x=0.3 components, the initial temperature of the blue shift of some Raman peaks in the x=0.5 sample is larger, and these results indicate that the spin-phonon coupling behavior in the RFeO3 material is related to the spin reorientation.
[0115] Fig. 9 (d) Fig. 9 (e) and Fig. 9 (f) shows Nd 0.7 Sm 0.3 FeO3 A g (2) B 2g (2) and A g (4) Peak position changes with temperature. Below 200K, the changes in the peak positions of all Raman peaks in the figure are mainly caused by the lattice expansion caused by temperature. g (2) and B 2g (2) The shift of the vibration mode can be attributed to the contribution of the spin-phonon coupling effect, which is in the range of 1 cm -1 -3cm -1Due to the limited test temperature range, it is difficult to determine other evolution trends at lower temperatures. The increase in spin-phonon coupling temperature may be due to the Sm 3+ The increase of spin reorientation temperature after doping. 3+ The introduction of Nd 3+ and Nd 3+ The interaction transforms into a more complex structure, thus changing the magnetic anisotropy. The increase in spin orientation temperature leads to a peak displacement plateau at higher temperatures, which is consistent with the Sm 0.5 Y 0.5 A similar situation was observed in FeO3.
[0116] In addition, we found that Nd 3+ The vibration of FeO6 along
[010] pc Therefore, this feature can be used to determine R from an empirical point of view 3+ The coupling between the vibration and FeO6 was confirmed by statistical analysis of the experimental results of temperature-dependent Raman spectroscopy. 3+ There is coupling with FeO6. Fig. 9 (g) Fig. 9 (h) and Fig. 9 In (i), B 2g (2) Mode and A g (4) The relationship between the modes as independent variables and the dependent variables. In the range of 80K-600K, the two modes of the three components are linearly correlated. A similar phenomenon is also observed in the x = 0.5 sample, where B cannot be distinguished at high temperatures. 2g (2) Mode, A g (2) The mode is the horizontal axis. Although we observed this important phenomenon, we only made this inference based on the Raman spectroscopy results, and the relationship between rare earth ions and oxygen octahedrons needs to be explored in more detail. This empirical behavior also has different tendencies in the three samples, and there is less relevant theory. The data points in the x = 0.5 sample are more scattered than those in the x = 0 and x = 0.3 samples. This may be caused by the quality of the spectrum; however, it cannot be ruled out that Sm 3+ / Nd 3+ The interaction between A and FeO6 is unknown. g (5) Mode and B 2g (2) Linear correlation is observed between the modes. 3+ The vibration mode is coupled with the multiple vibrations of FeO6 octahedron, and this coupling can explain to a certain extent the mechanism by which R-site exchange regulates the magnetic properties of RFeO3 materials.
[0117] From the above experiments, it can be seen that when the temperature changes, each vibration mode changes, and the temperature change affects the spin-phonon coupling effect. The change in this coupling effect will cause the magnetoresistance, superconductivity or magnetoelectric properties of the ferrite material to change. The present invention is an improvement based on this spin-phonon coupling effect, and pre-establishes the corresponding relationship between ferrite performance and temperature, so that in the later stage, the temperature of the ferrite can be adjusted according to performance requirements to achieve the target performance.
[0118] In the embodiments according to the present invention, the terms "first", "second", and "third" are only used for description and cannot be understood as indicating or implying relative importance; the term "plurality" refers to two or more, unless otherwise clearly defined. The terms "installed", "connected", "connected", "fixed" and the like should be understood in a broad sense. For example, "connected" can be a fixed connection, a detachable connection, or an integral connection; "connected" can be a direct connection or an indirect connection through an intermediate medium. For those of ordinary skill in the art, the specific meanings of the above terms in the embodiments according to the present invention can be understood according to specific circumstances.
[0119] In addition, although each operation is described in a specific order, this should be understood as requiring such operation to be performed in a specific order or in a sequential order, or requiring that all illustrated operations should be performed to obtain desired results. Under certain circumstances, multitasking and parallel processing may be advantageous. Similarly, although some specific implementation details are included in the above discussion, these should not be interpreted as limiting the scope of the present invention. Some features described in the context of a separate embodiment can also be implemented in a single implementation in combination. On the contrary, the various features described in the context of a single implementation can also be implemented in multiple implementations individually or in any suitable sub-combination mode.
[0120] Although the subject matter has been described in the language of specific structural features and / or method logical actions, it should be understood that the subject matter defined in the appended claims is not necessarily limited to the specific features or actions described above. On the contrary, the specific features and actions described above are merely example forms of implementing the claims.
[0121] The above are only preferred embodiments according to the embodiments of the present invention, and are not intended to limit the embodiments of the present invention. For those skilled in the art, various modifications and changes may be made according to the embodiments of the present invention. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the embodiments of the present invention shall be included in the protection scope of the embodiments of the present invention.
Claims
1. A method for regulating the performance of ferrite ceramics by 3d-4f superexchange interaction, characterized in that: The chemical formula of the ferrite ceramic is R1 1-x R2 x FeO3, 0≤x≤1, R1 and R2 are both rare earth elements, and the method for regulating the performance of ferrite ceramics by 3d-4f super exchange includes: The ferrite ceramic is heated for multiple times, and the temperature of the ferrite ceramic after any two heatings is different, and the ferrite ceramic is tested after each heating, and the performance parameters of the ferrite ceramic at different temperatures are determined; Establishing a corresponding relationship between the performance parameter and the temperature of the ferrite ceramic; Based on the input of the target performance parameter of the ferrite ceramic, determining the target temperature of the ferrite ceramic according to the target performance parameter and the corresponding relationship; The ferrite ceramic is adjusted to the target temperature so that the ferrite ceramic has target performance.
2. The method for regulating the performance of ferrite ceramics by 3d-4f superexchange according to claim 1, characterized in that: x≠0, and x≠1, the method for regulating the performance of ferrite ceramics by 3d-4f superexchange interaction further comprises: R12O3, R22O3 and Fe2O3 are mixed and ball-milled in anhydrous ethanol to form a mixture. The mixture is dried by an evaporator, and the dried mixture is calcined at a first preset temperature for a first preset time. The calcined mixture is ball-milled for a second time in anhydrous ethanol, and the mixture after the second ball-milling is dried to obtain an intermediate powder. The intermediate powder is mixed with a PVA solution and then ground and pressed into a ceramic sheet by a tablet press. The ceramic sheet is placed in a muffle furnace and kept warm at a third preset temperature for a third preset time to obtain the ferrite ceramic.
3. The method for regulating the performance of ferrite ceramics by 3d-4f superexchange according to claim 2, characterized in that: The R1 is a Nd element, and the R2 is a Sm element; The first preset temperature is greater than or equal to 900° C. and less than or equal to 1000° C.; The first preset duration is greater than or equal to 5 hours and less than or equal to 7 hours; The third preset temperature is greater than or equal to 1200° C. and less than or equal to 1300° C.; The third preset duration is greater than or equal to 5 hours and less than or equal to 7 hours.
4. The method for regulating the performance of ferrite ceramics by 3d-4f superexchange according to claim 2, characterized in that: Before the step of keeping the temperature at the third preset temperature for the third preset time, the method further includes: Keep warm at a second preset temperature for a second preset time; Heating the temperature in the muffle furnace to the third preset temperature according to a first heating rate; The second preset temperature is greater than or equal to 600° C. and less than or equal to 700° C., the second preset time is greater than or equal to 2 h and less than or equal to 4 h, and the first heating rate is less than or equal to 3° C. / min.
5. The method for regulating the performance of ferrite ceramics by 3d-4f superexchange according to claim 1, characterized in that: The performance parameter includes one of the following: a magnetoresistance performance parameter, a superconductivity performance parameter or a magnetoelectric performance parameter.
6. The method for regulating the performance of ferrite ceramics by 3d-4f superexchange according to claim 1, characterized in that: The chemical formula of the ferrite ceramic is one of the following: NdFeO3, Nd 0.9 Sm 0.1 FeO3、Nd 0.8 Sm 0.2 FeO3、Nd 0.7 Sm 0.3 FeO3、Nd 0.6 Sm 0.4 FeO3 and Nd 0.5 Sm 0.5 FeO3.
7. The method for regulating the performance of ferrite ceramics by 3d-4f superexchange according to claim 1, characterized in that: The test experiment includes one or a combination of the following: Four-probe measurement experiment, resistance-temperature curve measurement experiment, magnetoelectric effect measurement experiment, XPS test experiment, hysteresis loop analysis experiment, UV-diffuse reflectance absorption spectrum test experiment, non-polarized Raman spectrum analysis experiment.
8. The method for regulating the performance of ferrite ceramics by 3d-4f superexchange according to claim 7, characterized in that: The steps of the non-polarized Raman spectroscopy analysis experiment specifically include: A Raman scattering test is performed on the ferrite ceramic at room temperature using a laser with a wavelength of 532 nm through a microscopic confocal Raman spectrometer to obtain test data, and the test data is fitted through data fitting software to obtain a curve graph.
9. The method for regulating the performance of ferrite ceramics by 3d-4f superexchange according to claim 8, characterized in that: The curve graph includes one of the following or a combination thereof: a Raman shift-temperature curve, a half-peak width-temperature curve, a Raman scattering intensity-temperature curve, and a vibration mode curve.
10. The method for regulating the performance of ferrite ceramics by 3d-4f superexchange according to claim 7, characterized in that: The test mode of the hysteresis loop analysis experiment is the FC-ZFC mode, the external magnetic field is 100 Oe, and the temperature range is 2K to 400K.